Penguatan Kesiapsiagaan Bencana Gempabumi di Sekolah Luar Biasa SLB/C Amal Mulia Jakarta Selatan Melalui Poster Rute Evakuasi untuk Siswa Berkebutuhan Khusus - Jeremy Putra Pratama; Ari Yuda Caesar Sutikno; Muhamad Shafar Nur Rahman; M. Syahrul Rezi; Amal Ramadhani Putra; Fathin Aulia Rahman; Abdul Haris Achadi; Imelda Imelda (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Disaster preparedness in special schools (SLB) is crucial to protect students with special needs. The purpose of this community service is to improve the knowledge and preparedness of SLB/C Amal Mulia Jakarta Selatan students in dealing with earthquake disasters. The method used is a participatory approach involving students, teachers, and school staff in counseling, creating instructional media in the form of evacuation route maps with bright colors, and conducting evacuation simulations. The results showed significant improvements in students' knowledge. On the Earthquake Definition parameter, there was an 800% increase, while the "Impact of Earthquakes" increased by 166%. Significant increases were also recorded on knowledge about types of disasters (28.57%) and correct evacuation procedures, with an increase of 1700%. The use of instructional media in the form of brightly colored evacuation route posters proved effective in helping students understand the evacuation routes. Overall, this activity successfully improved disaster preparedness at SLB Amal Mulia, preparing students to respond to emergencies with greater readiness and safety.